Interference alignment based on optimizing bit allocation with limited feedback in interfering MIMO-MAC networks - Xian-zhong XIE; Dan LI; Wei-jia LEI; Sen-lin ZHANG (Tongxin xuebao)
A novel limited feedback for interference alignment algorithm was proposed based on the disadvantages of traditional limited feedback interference alignment schemes for MIMO uplink.Unlike the traditional linear interference alignment,an iterative scheme was presented.The pre-coder was designed through maximizing the target signal to the interference leakage and noise ratio,and interference suppression matrix was designed by maximizing the signal to interference plus noise ratio for each data stream,which can come over rate loss in low SNR.In addition,the bit allocation of traditional limited feedback schemes were based on the mean of interference leakage,which were not perfect and make the total number of the effective bits less than the bits provided by system.Thus,a novel bit allocation scheme was provided that improving bit utilize and decreasing quantization error.Theoretical analysis and simulation experiments show that compare to the existed classical algorithms,the algorithm was a stepwise enhancement of signal quality for iterative search in perfect CSI which was better than linear algorithm and has a larger space with no need for strictly align interference in limited feedback CSI which reduces the influence of quantization error more.The effective bit distribution and bit utilization are improved by bit allocation,resulting in improved performance in limited feedback.